THE FORMS OF PHONOLOGICAL INTERFERENCE OF BALINESE LANGUAGE SPOKEN IN PANGSAN VILLAGE TOWARD ENGLISH LANGUAGE - I Gusti Putu Agus Edy Eka Putra (Universitas Samudra, 2022)
This study aims analyze the interference of the Phonology of the Balinese in Pangsan village towards English. The research is a type of qualitative research. The research methods and techniques consist of the methods and techniques of providing data, the methods and techniques of data analysis, and the methods and techniques of presenting data. The data collection in this study was done by asking native speakers of Pangsan village to read English-language words and the researchers recorded, the words was randomly selected by the researchers so that the instructor had no preparation to learn the pronunciation of the sound of the words. As for the method in analyzing the data of this research is the equivalent method, which is a type of articulatory phonetic equivalent method. The method used to convey the results of research is formal and informal methods. Based on the results of the study, it was found that the phonological interference of the Balinese language was realized by Pangsan Village towards English.